2016
DOI: 10.1016/j.jbiotec.2016.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Refined Pichia pastoris reference genome sequence

Abstract: Strains of the species Komagataella phaffii are the most frequently used “Pichia pastoris” strains employed for recombinant protein production as well as studies on peroxisome biogenesis, autophagy and secretory pathway analyses. Genome sequencing of several different P. pastoris strains has provided the foundation for understanding these cellular functions in recent genomics, transcriptomics and proteomics experiments. This experimentation has identified mistakes, gaps and incorrectly annotated open reading f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
86
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(89 citation statements)
references
References 78 publications
3
86
0
Order By: Relevance
“…Similarly, Sturmberger et al (23) found 24 differences (SNPs and indels) between CBS7435 and paired-end Illumina HiSeq reads of BioGrammatics' strains BG08 and BG10, stating that "Only small clonal variations occur between these closely related P. pastoris strains, even after storage at different sites for many years, indicating defined molecular manipulation can be precise with relatively little clonal drift." Many of the indels are in repetitive regions and thus could reflect the differences in short Illumina read (used in this study) and long PacBio read (used for obtaining the reference sequence [23]) sequencing technologies (52) to correctly sequence repetitive and GC-rich regions. Even though these mutations obtained quality scores of Ͼ20, which primarily indicates that all of the reads that mapped to that region had the same change in it compared to the reference, the change could still also represent technical bias arising from the sequencing method used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Sturmberger et al (23) found 24 differences (SNPs and indels) between CBS7435 and paired-end Illumina HiSeq reads of BioGrammatics' strains BG08 and BG10, stating that "Only small clonal variations occur between these closely related P. pastoris strains, even after storage at different sites for many years, indicating defined molecular manipulation can be precise with relatively little clonal drift." Many of the indels are in repetitive regions and thus could reflect the differences in short Illumina read (used in this study) and long PacBio read (used for obtaining the reference sequence [23]) sequencing technologies (52) to correctly sequence repetitive and GC-rich regions. Even though these mutations obtained quality scores of Ͼ20, which primarily indicates that all of the reads that mapped to that region had the same change in it compared to the reference, the change could still also represent technical bias arising from the sequencing method used.…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of next-generation whole-genome sequencing (WGS), reference genomes (20)(21)(22) and refined sequencing and annotations (23)(24)(25) have become available for different P. pastoris wild-type strains. With further decreases in the cost of these technologies, systematic studies of the underlying mechanisms for clonal variation in P. pastoris transformants have become feasible.…”
mentioning
confidence: 99%
“…Sequences resembling known killer proteins can also be searched for in whole‐genome or environmental metagenomic data. For example, sequences homologous to those in Kluyveromyces lactis killer plasmids were recently identified using whole‐genome sequencing data from Pichia pastoris (Sturmberger et al, ). Toxin‐coding genes have also been found in environmental bacterial metagenomic datasets (Slaby, Hackl, Horn, Bayer, & Hentschel, ) and may be detectable in similar fungal datasets.…”
Section: How Do Researchers Find Killer Yeasts?mentioning
confidence: 99%
“…Sequence information about the target locus is a prerequisite for gene replacement by HR. During the last years, whole genome sequences of important P. pastoris strains (e.g., GS115, DSMZ 70382, and CBS 7435) have become available (De Schutter et al, ; Mattanovich et al, ; Sturmberger et al, ), which drastically facilitated genomic engineering of P. pastoris . Unfortunately, targeted disruption, insertion, or replacement of genes has proven to be problematic in P. pastoris (Schwarzhans et al, ).…”
Section: Introductionmentioning
confidence: 99%